Patterning the peripheral retina of the fly: decoding a gradient. - Tomlinson, A. (Developmental Cell, 2003)
The peripheral regions of the fly eye show a number of specializations. First, immediately interior to the circumscribing head capsule and completely encircling the rest of the eye lies a thick band of pigment cells (pigment rim; PR). Second, in the dorsal periphery of the eye directly interior to the PR lie the dorsal rim (DR) ommatidia that are specialized polarized light detectors. The equivalent position in the ventral eye is occupied by standard ommatidia. Third, ommatidia characteristically project mechanosensory hairs above their lenses, but in the most peripheral rows (including the DR) the ommatidia are bald. Wingless secreted from the head capsule appears to organize all these peripheral specializations. Higher Wg levels induce PR, intermediate levels induce DR, and lower levels induce baldness. The predisposition of dorsal cells to generate DR ommatidia appears to be endowed by the exclusive dorsal expression of Iroquois genes.